Salix transect of Europe: patterns in the distribution of willow-feeding psyllids (Hemiptera: Psylloidea) from Greece to arctic Norway - Percy, Diana; Cronk, Quentin (Biodiversity Data Journal, 2020)
Background Psyllids are oligophagous phytophagous insects with many specialist willow ( Salix spp.) feeding species in two genera ( Cacopsylla and Bactericera ). We examine the patterns of distribution and co-occurrence of willow-feeding species at 42 willow sites across Europe forming a transect from Greece (lat. 38.8 °N) to arctic Norway (lat. 70.6 °N). The transect and sites have been described in previous papers. New information A total of 1245 individual psyllids were examined from 23 species of willow over the transect, representing 17 willow-feeding species (11 Cacopsylla and 6 Bactericera ). Numerous species were very widely distributed, with two species, Bactericera albiventris (Foerster, 1848) and Cacopsylla pulchra (Zetterstedt, 1840), occurring from Greece to Finland. Other widespread species (Romania to Finland) were Cacopsylla ambigua (Foerster, 1848) and Bactericera curvatinervis (Foerster, 1848). The mean number of psyllid species per site was 2.4 (1.3 Cacopsylla , 1.1 Bactericera ).